Successful Treatment of Anti-MDA5 Antibody-Positive Dermatomyositis-Associated Rapidly Progressive-Interstitial Lung Disease by Plasma Exchange: Two Case Reports. Issue 14 (July 2021) - Takahashi, Rina; Yoshida, Tadashi; Morimoto, Kohkichi; Kondo, Yasushi; Kikuchi, Jun; Saito, Shuntaro; Ishigaki, Sho; Kaneko, Yuko; Takeuchi, Tsutomu; Itoh, Hiroshi; Oya, Mototsugu
Background: Patients with anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive dermatomyositis (DM) are frequently accompanied by rapidly progressive-interstitial lung disease (RP-ILD). They are often refractory to intensive immunosuppressive therapy and have poor prognosis. Case presentation: A 73-year-old woman presented with fever, cold symptoms, and skin eruption for a month. She also exhibited muscle weakness on upper extremities slightly. The titer of anti-MDA5 antibody was extremely high, and computed tomography showed ground glass opacity and reticular shadows in the lungs. She was diagnosed as anti-MDA5 antibody-positive classical DM-associated RP-ILD and treated with intensive immunosuppressive therapy. However, the titer of anti-MDA5 antibody did not decrease satisfactorily, and plasma exchange was alternatively initiated. The titer decreased remarkably, and she obtained disease remission. Similarly, a 63-year-old woman presented with stiffness of the neck and hands, fever and cough. She was also diagnosed as anti-MDA5 antibody-positive classical DM-associated RP-ILD, because she had skin eruptions, slight muscle weakness, an elevation in anti-MDA5 antibody, and RP-ILD. She was unresponsive to intensive immunosuppressive therapy, but plasma exchange successfully improved the titer of anti-MDA5 antibody, the symptoms, and the findings of computed tomography. Conclusions: Although anti-MDA5 antibody-positive DM-associated RP-ILD has a high mortality rate, this report suggests the usefulness of plasma exchange to improve the prognosis.